2003
DOI: 10.1038/sj.npp.1300193
|View full text |Cite
|
Sign up to set email alerts
|

Toluene-Induced Locomotor Activity is Blocked by 6-Hydroxydopamine Lesions of the Nucleus Accumbens and the mGluR2/3 Agonist LY379268

Abstract: The abuse of volatile inhalants remains a prominent, yet poorly understood, form of substance abuse among youth. Nevertheless, the identification of a mechanism underlying the reinforcing properties of inhalants has been hampered by the lack of a clearly identifiable neural substrate upon which these chemicals act. One ingredient that is common to many abused inhalants is toluene, an organic solvent that is self-administered by nonhuman primates and rodents. Most drugs of abuse have been found to elicit forwar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
44
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 55 publications
6
44
0
Order By: Relevance
“…In accordance with our results, other studies have shown that acute inhalation and systemic toluene administration increases locomotion [7,13,44]. The sensitization that we observed after postnatal chronic toluene exposure (A/T) is also in line with the observation that sensitization occurs after binge toluene exposure in mice and rats [4,13,14,30].…”
Section: Locomotor Effectssupporting
confidence: 93%
“…In accordance with our results, other studies have shown that acute inhalation and systemic toluene administration increases locomotion [7,13,44]. The sensitization that we observed after postnatal chronic toluene exposure (A/T) is also in line with the observation that sensitization occurs after binge toluene exposure in mice and rats [4,13,14,30].…”
Section: Locomotor Effectssupporting
confidence: 93%
“…Thus, actions at these receptors may potentially contribute to the effects of LY379268 at high doses. However, the present results are not likely to be attributable to the action of LY379268 on receptors other than mGlu2/3 receptors because of the low dose (1 mg/kg) of LY379268 used in this study compared doses (3-10 mg/kg) frequently used in the literature to observe reliable behavioral or neurochemical effects (Cartmell et al, 2000a-c; Riegel et al, 2003).…”
Section: Discussionmentioning
confidence: 62%
“…This hypothesis is supported by the observation that mGlu2/3 receptors are expressed in the NAcc shell (Testa et al, 1998), and these receptors regulate both basal and psychostimulantinduced NAcc dopamine neurotransmission (Greenslade and Mitchell, 2004;Hu et al, 1999;Karasawa et al, 2006;Kim et al, 2005;Manzoni et al, 1997;Uslaner et al, 2009;Xi et al, 2002aXi et al, , 2010a. Furthermore, activation of mGlu2/3 receptors attenuated the dopamine-dependent psychostimulant-induced enhancement of locomotor activity (Kim et al, 2005;Riegel et al, 2003).…”
Section: Introductionmentioning
confidence: 92%
“…During at least one of the later sessions, one or more concentrations of toluene increased activity, compared to air and compared to initial toluene exposure, in rats of all ages and both sexes. While a few previous studies have reported the development of sensitization after repeated exposure of adult male rodents to inhaled [62,63] or systemically administered toluene [40][41][42], the present study is perhaps the first to examine the effects of toluene in a sensitization paradigm in adolescent rats. Our results here reveal that development of sensitization to the locomotor stimulant effects of toluene in adolescent rats of both sexes was minimal and did not occur until the second week of exposure sessions.…”
Section: Discussionmentioning
confidence: 94%
“…Development of the sensitization to the elevated locomotor activity seen in rats treated repeatedly with stimulants has been demonstrated to be mediated by dopaminergic activation [38]. Interestingly, there is now evidence that dopaminergic systems may also play a role in the acute, and possibly the long term, effects of toluene on locomotor activity as well [40][41][42]. Indeed, cross-sensitization has been shown from cocaine to toluene [3].…”
Section: Discussionmentioning
confidence: 99%